Inter-professional collaboration in an Intensive Care Unit: Challenges and opportunities - Eveline Rodrigues da Silva Barros; Ana Ecilda Lima Ellery (Rev Rene)
Objective: to understand the relationship between health professionals in an intensive care unit, to explore the inter-professional collaboration. Methods: it is a qualitative study, inspired by the Hermeneutics Phenomenology of Paul Ricoeur, for the production of knowledge. Interviews were conducted with 36 intensive care professionals of a tertiary public hospital. Results: the professionals are satisfied with the work, and there is a commitment to provide quality care despite organizational boundaries such as precarious employment relationships and turnover of professionals. The inter-professional collaboration is an indispensable factor for assistance, but in practice is not effective most of the times by the absence of provisions for the integration of the team, leadership presence, as well as the overcrowding of services that overwhelm health workers. Conclusion: while recognizing the need for inter-professional collaboration, professionals do their work even in a very individualized way, with no strategies to boost this cooperation.